What were the drivers of hinterland exhumation during flat-slab subduction in the southern Central Andes? Insights from multi-sample thermal history modeling using hefty 2.0 and fetkin software - Mackaman Lofland, Chelsea (2022)
Flat-slab subduction is acornerstone tectonic process, commonly linked to changes in convergent marginthermal structure, enhanced seismicity, and intraplate shortening and magmatismexpressed hundreds of kilometers from the trench. Yet, the impacts of flat-slabsubduction on hinterland evolution remain poorly understood. We leverage newthermochronological data from the Argentine Frontal Cordillera (a zone of highhinterland topography above the modern flat-slab segment at 29–33ºS) and novelthermal history modeling techniques to interrogate the influence of (1)increased plate coupling, elevated shortening, and structurally-drivenexhumation along emergent or subsurface faults, and/or (2) dynamic upliftassociated with slab flattening and inboard migration of the subduction hinge.New apatite and zircon (U-Th)/He data quantify hinterland cooling duringPaleogene subduction and Neogene flattening of the Nazca oceanic plate. Ourthermal history modeling approach implements a time-elevation extension to the1D HeFTy thermal history modeling program that allows simultaneous inversion ofmultiple samples along a structural or topographic profile. This extensionenables HeFTy to better approximate transient effects such as isothermcompression during rapid exhumation and the transition from geothermal toelevation gradients, and allows for change in the relative depth among samples(e.g., tilting, folding) during the history within user-defined constraints.Multi-sample modeling results from hinterland sample profiles spanning analong-strike distance of >400 km record rapid exhumational cooling coevalwith middle Miocene flattening of the subducted slab, and point tostructurally-driven exhumation: along an orogen-scale fault-bend fold anticlineat 29–31°S, and emergent faults that exhume west-dipping hanging wall panels at~31–33°S. We illustrate the resulting structural, topographic, andthermochronological relationships along two reconstructed 2D geological crosssections using thermokinematic modeling (FETKin software). This researchdemonstrates the utility of multi-sample thermal history modeling in refiningthe results obtained from single-sample modeling approaches, and evaluating thetiming, rates, and drivers of exhumation during changes in subduction.